Acceptance of Halodoc’s Online Teleconsultation During Covid-19 - Amelia Andriani; Margaretha Pink Berlianto (Enrichment : Journal of Management, 2022)
This research aims to analyse the positive effect of performance expectancy, effort expectancy, social influence, attitude toward using technology, perceived ease of use, and perceived usefulness on behaviour intention, the positive effect of behaviour intention on usage behaviour. This study used quantitative research and data collection was collected using questionnaire. The target population of this research were people that have done online teleconsultation at Halodoc and willing to be respondents of this research. The number of samples were determined to be which 224 samples. The sampling technique use was purposive sampling. Partial Least Square-Structural Equation modelling (PLS-SEM) is applied to this study. The results of data analysis showed all of the hypothesis supported that performance expectancy, effort expectancy, social influence, attitude toward using technology, perceived ease of use, and perceived usefulness have positive effect on behaviour intention. Lastly, behaviour intention has a positive effect on usage behaviour in acceptance of Halodoc’s online teleconsultation during COVID-19.